Effectiveness of digital media for basic life support training among laypersons: A systematic review - Hasami, Muhammad Riandi; Kamaluddin, Ridlwan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Basic Life Support (BLS) training among laypersons plays a crucial role in improving survival rates following out-of-hospital cardiac arrest. Early cardiopulmonary resuscitation (CPR) performed by bystanders can significantly increase the likelihood of survival. However, conventional face-to-face training is often limited by accessibility, time constraints, and resource availability. The rapid development of digital technology offers alternative approaches to delivering BLS education that may overcome these barriers. Purpose: To examine the effectiveness of digital media in BLS training among laypersons, particularly in improving knowledge and practical skills related to CPR. Method: This systematic review was conducted in accordance with the PRISMA guidelines. A comprehensive search was performed in Scopus, PubMed, ScienceDirect, CINAHL, Crossref, and Google Scholar for studies published between January 2020 and December 2025. Eligible studies evaluated digital media–based BLS training for laypersons and reported outcomes related to knowledge or skill performance. The methodological quality of included studies was assessed using the JBI Critical Appraisal Checklist. This review was registered in PROSPERO (CRD420251249898). Results: Seven studies met the inclusion criteria. The findings consistently indicated that digital media, particularly virtual reality and video-based learning, were effective in enhancing participants’ knowledge and practical BLS skills. Several studies also reported improved engagement and accessibility compared to conventional training methods. Nevertheless, variations in instructional design, content quality, and evaluation methods influenced the overall effectiveness of the interventions. Conclusion: Digital media represents a promising approach to BLS training among laypersons. When appropriately designed, digital interventions can enhance learning outcomes, increase accessibility, and support independent practice. Future research should explore long-term skill retention and standardized outcome measures to strengthen the evidence base.